Spicy Herb Extracts as a Potential Improver of the Antioxidant Properties and Inhibitor of Enzymatic Browning and Endogenous Microbiota Growth in Stored Mung Bean Sprouts - Małgorzata Sikora; Urszula Złotek; Monika Kordowska-Wiater; Michał Świeca (MDPI AG, 2021)
The quality and shelf life of sprouts can be improved by postharvest application of water herb extracts. The effect of water infusions of marjoram, oregano, basil, and thyme on the phenolic content, antioxidant potential, and the microbiological and consumer quality of stored mung bean sprouts was studied. Compared to the control, the treatments increased total phenolic content. The highest amounts were determined in sprouts soaked in the thyme extract (6.8 mg/g d.m.). The infusions also inhibited the activity of enzymes utilizing phenolics, and marjoram and oregano were found to be the most effective. The increase in the level of phenolics was reflected in enhanced antioxidant properties (ability to quench cation radical ABTS•+, reducing and chelating power). Both total phenolics and flavonoids, as well as antioxidant capacities, were highly bioaccessible in vitro. All the natural extracts effectively reduced the growth of total mesophilic bacteria, coliforms, and molds (they were more effective than ascorbic and kojic acids). The treatments did not exert a negative influence on the sensory properties or nutritional value of the sprouts, and even improved starch and protein digestibility. These results are very promising and may suggest a wider used of natural extracts as preservatives of minimally processed food.